2012
DOI: 10.1093/rheumatology/kes129
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular adipose-derived mesenchymal stem cells from rheumatoid arthritis patients maintain the function of chondrogenic differentiation

Abstract: Objectives. To evaluate the chondrogenic potential, phenotype and percentage of IA adipose-derived mesenchymal stem cells (ADSCs) from RA patients in comparison with OA patients. The effect of TNF treatment on ADSC differentiation was also examined. Methods. Adipose tissue was obtained from RA and OA patients. ADSCs were isolated and cultured until passage 4. After that period, the phenotype and percentage of these cells were analysed by flow cytometry. Passage 4 cells were cultured in chondrogenic medium with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
3
19
0
3
Order By: Relevance
“…According to previous reports, the chondrogenic potential of passaged synovial MSCs in RA patients was similar to that in OA patients by Skalska et al [22] and Koizumi et al [23], contrarily, that in RA patients was inferior to that in OA patients by Jones et al [19]. Jones et al collected synovial tissues for biopsy and CRP in donors ranging between 0 and 15 mg/dl, contrarily the other studies, including ours, collected synovial tissues primarily during total knee arthroplasty and CRP in donors ranging only between 0 and 8 mg/dl.…”
Section: Discussionsupporting
confidence: 75%
“…According to previous reports, the chondrogenic potential of passaged synovial MSCs in RA patients was similar to that in OA patients by Skalska et al [22] and Koizumi et al [23], contrarily, that in RA patients was inferior to that in OA patients by Jones et al [19]. Jones et al collected synovial tissues for biopsy and CRP in donors ranging between 0 and 15 mg/dl, contrarily the other studies, including ours, collected synovial tissues primarily during total knee arthroplasty and CRP in donors ranging only between 0 and 8 mg/dl.…”
Section: Discussionsupporting
confidence: 75%
“…In our previous publications, we have reported that TNF is able to inhibit chondrogenesis of AAT-ASCs from RA and OA patients [21]. We have also shown that TNF has complex effect on AAT-ASCs osteogenesis: it up-regulates early osteogenesis markers mRNA expression and enhances calcium deposition, but decreases expression of mRNA coding for non-mineral bone components [22].…”
Section: Discussionmentioning
confidence: 84%
“…Tkankę tłuszczową białą i brunatną zasiedlają somatyczne komórki macierzyste pochodzenia mezenchymalnego [19]. Jest ona tanim, nieograniczonym rezerwuarem komórek macierzystych -z 300 ml tkanki tłuszczowej uzyskuje się 2-3 × 10 8 ADSCs, czyli od 100 do 1000 razy więcej niż mezenchymalnych komórek macierzystych ze szpiku kostnego [11,20].…”
Section: Mezenchymalne Komórki Zrębu Tkanki Tłuszczowej (Ang Adipocyunclassified
“…To parakrynne wydzielanie cytokin tłumaczy ich duże stężenia u osób otyłych [22]. Mezenchymalne komórki zrębu tkanki tłuszczowej mogą się różni-cować również w osteoblasty, chondrocyty, miocyty oraz komórki neuronów, co daje ogromne możliwo-ści ich zastosowania w medycynie regeneracyjnej [11,19,20]. Obecnie wykorzystuje się je w dermatologii estetycznej do zabiegów odmładzania skóry, wygła-dzania zmarszczek, lipoatrofii twarzy oraz w seksuologii (poprawiają erekcję).…”
Section: Figure 1 Sources Of Stem Cells In the Epidermis And Hair Founclassified
See 1 more Smart Citation